PENINGKATAN KETERAMPILAN MENULIS TEKS PIDATO MELALUI MODEL PEMBELAJARAN KONTEKSTUAL PADA SISWA KELAS VII MTs AN-NUR TAHUN PELAJARAN 2023/2024 - Moh Ari Wibowo; Barrotul Qomariyah; Sahrul Muzekki (Jurnal Cendekia Pendidikan, 2024)
Writing skills are very important skills in life, not only in educational life but also very important in social life. Writing skills are taught with the aim that students are able to write well and correctly, therefore writing is called a productive and expressive activity. Therefore, the researcher raised the title "Improving speech text writing skills through a contextual learning model for class VII students at MTs An-Nur for the 2023/2024 academic year. thesis." Aims to describe the improvement in speech text writing skills for class VII MTs An-Nur Pakalongan semester 1 of the 2023/2024 academic year using a contextual learning model. This research is classroom action research. The variable of this research is speech text writing skills through a contextual learning model. The research sample was class VII, totaling 18 students, 10 women and 8 men. Data collection techniques used speech writing texts. The results of calculating the class average in cycle I recorded that the average student writing ability was 76 and had reached the specified KKM score of 75. Meanwhile, the completeness of student learning outcomes in cycle I was 17% or a total of 18 students in class VII MTs An-Nur completed. . In cycle II, it was recorded that the average score for students' writing ability was 78, which was above the KKM score in the Indonesian language subject, namely 75. And completion reached 80.85%, already above 75%.